Relevasi Pendekatan Saintifik dengan Konsep Sains pada Anak Usia Dini - Izzuddin, Ahmad (MASALIQ, 2023)
The scientific approach strongly supports children's cognitive and language development. Children's cognitive development is very closely related to reason and thought so that growth in this area has a very wide range. There are various abilities of children in the cognitive field that must be developed, one of which is science. Science is knowledge that is systematically arranged which is obtained from a series of experiments and observations that can be tested further. Science is currently a very important thing to introduce to young children because science can invite children to think logically and critically. This study aims to find out how the relevance of the scientific approach to the concept of science in early childhood. This research is descriptive qualitative. The research results show that there is a very significant relevance between the scientific approach and the concept of early childhood science, with the scientific approach raising children's motivation to learn through play.